The precursory information of acoustic emission during sandstone loading based on critical slowing down theory. (26th June 2018) - Wei, Yang; Li, Zhonghui; Kong, Xiangguo; Zhang, Zhibo; Cheng, Fuqi; Zheng, Xiangxin; Wang, Cong
Abstract: In order to study the critical slowing down characteristics of acoustic emission signals produced by the failure of the sandstone, the YAW4306 computer controlled electro-hydraulic servo press and the CTA-1 type acoustic emission data acquisition system were used to carry out the sandstone uniaxial compression experiment. The experiment results show that the acoustic emission signals produced by the destruction of sandstone have obvious stage characteristics and the cumulative acoustic emission count has good correspondences with the damage of sandstone. The increase of slope of the cumulative count curve of the acoustic emission indicates that the destruction of sandstone is coming. The autocorrelation coefficient and the variance of the critical slowing down characteristics are studied in different lag step lengths and window lengths. It can be found that different window lengths and lag step lengths have influences on the autocorrelation coefficient and the variance. When the window length is equal, the autocorrelation coefficient cures corresponding to different lag step lengths are messy and are consistent only in some parts, and the corresponding variance cures are basically coincident. Before the sample is destroyed, the small increases of the variance curve represent the occurrence of large cracks. The sudden and large-scale increase of the autocorrelation coefficient and the variance of the acoustic emission count can be used as the precursor signal of the destruction of the sandstone sample. Compared with the autocorrelation coefficient, the precursor signal of variance is more obvious. This is of great theoretical and guiding significance for enriching and improving the acoustic emission monitoring technology of rock mass.